The nitric oxide‐cyclic guanosine monophosphate pathway inhibits the bladder ATP release in response to a physiological or pathological stimulus - Okuyama, Eriko (Physiol Rep, 2021)
The release of ATP from the epithelium of the urinary bladder (urothelium) in response to mechanical/chemical stimuli contributes to the visceral sensation in the micturition reflex. The nitric oxide (NO)‐mediated induction of cyclic guanosine monophosphate (cGMP) has been detected in urothelial cells and may inhibit the micturition reflex. However, the function of the NO‐cGMP pathway in the regulation of urothelial ATP release remains poorly understood in contrast to its effects on smooth muscles or primary afferent nerves. Therefore, we investigated the relevance of the NO‐cGMP pathway to ATP release on the mucosal side in the present study. The administration of l‐arginine (NO precursor) or NOC 12 (NO donor) significantly reduced ATP release to the mucosal side at a physiologically normal urine storage pressure (5 cmH(2)O). L‐NAME (NO synthase inhibitor) significantly increased the distention‐induced release of ATP. The phosphodiesterase‐5 inhibitor, sildenafil, which increases cGMP levels, inhibited distention‐induced ATP release. Furthermore, sildenafil significantly reduced ATP release in response to the administration of lipopolysaccharide. These results suggest that the NO‐cGMP pathway inhibited urothelial ATP release during the storage phase under both physiological and pathological conditions.